Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd001735.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Support surfaces for pressure ulcer prevention

Abstract: Background Pressure ulcers (i.e. bedsores, pressure sores, decubitus ulcers) are areas of localised damage to the skin and underlying tissue. They are common in the elderly and immobile, and costly in financial and human terms. Pressure-relieving support surfaces (i.e. beds, mattresses, seat cushions etc) are used to help prevent ulcer development. Objectives This systematic review seeks to establish: (1) the extent to which pressure-relieving support surfaces reduce the incidence of pressure ulcers compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 110 publications
1
52
0
2
Order By: Relevance
“…All were found to be genuinely uncertain with the exception of one patient submission. A systematic review found reliable evidence for the use of medical grade sheepskins for the prevention of pressure ulcers 180 and so this was removed from the list. Partial evidence was found to answer two uncertainties submitted by patients and clinicians: the effectiveness of support surfaces for prevention and the use of nutritional interventions for prevention.…”
Section: Collationmentioning
confidence: 99%
See 1 more Smart Citation
“…All were found to be genuinely uncertain with the exception of one patient submission. A systematic review found reliable evidence for the use of medical grade sheepskins for the prevention of pressure ulcers 180 and so this was removed from the list. Partial evidence was found to answer two uncertainties submitted by patients and clinicians: the effectiveness of support surfaces for prevention and the use of nutritional interventions for prevention.…”
Section: Collationmentioning
confidence: 99%
“…13 that compression is an effective intervention for healing venous leg ulcers 184 and that higher-specification foam mattresses reduce the incidence of pressure ulceration compared with standard hospital foam mattresses. 180 This said, it should be acknowledged that the standard systematic review methods can be restrictive as they are based mainly on pairwise comparisons and group-level data. Other, more advanced, systematic review and meta-analysis methods are now available that may be more informative in areas of persisting uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dynamic support surfaces purports to cause a reduction in pressure ulcer formation in high risk patients (Inma et al, 1993). However, the effectiveness of existing dynamic support surfaces in reducing incidence of pressure ulcers remains controversial (Reddy et al, 2006;McInnes et al, 2011;Qaseem et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, all existing dynamic support surfaces are based on regular patterns of supports with no optimization of support array, size, shape, etc. While there are several dynamic interfaces in use currently, there is no definitive evidence of enhanced pressure ulcer prevention with their use (Reddy et al, 2006;McInnes et al, 2011;Qaseem et al, 2015). Furthermore, the support array sizes, shapes and patterns for dynamic support surfaces has not been optimized.…”
Section: Introductionmentioning
confidence: 99%
“…while awaiting surgery or immediately afterwards) may benefit from the use of an alternating pressure mattress, but this should never replace the need for repositioning (see keep moving below). The relative merits of these higher specification support surfaces in preventing pressure injuries are unclear [11]. Once the patient can sit out of bed, it is essential that risk of pressure injuries is still acknowledged and a pressure redistributing cushion is used until the patient is fully mobile.…”
Section: Evidence-based Preventive Interventionsmentioning
confidence: 99%